Analisis KUHPerdata Pasal 345 Terhadap Permohonan Perwalian Atas Anak Dari Saudara Kandung: Studi Putusan Nomor 375/PDT.P/2023/PA.SGM - Muhammad Imam Drajat; Tamaulina Br. Sembiring (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
In life, of course, there are those who are born and there are those who die, so this affects the guardianship of children, in this case as in decision 375/PDT. P/2003/PA. SGM where the biological father is still alive, but the deceased mother's siblings request guardianship over the child, even though it is clearly seen in Article 345 of the Civil Code that states that if one of the parents dies then the guardianship rights over the minor child automatically fall to his surviving parents. However, the decision handed down by the panel of judges was different in this case, which granted the child's aunt to be his guardian, so this attracted the writer's attention to research this matter more deeply. This research is qualitative research with a normative juridical type of research, using two approaches, namely the statutory approach and the Conceptual Approach. The results of this research prove that the position of the biological father of the child for whom guardianship is requested in this decision does not meet the requirements because he stated that he was no longer able to care for or care for the child, which is in accordance with Article 391 (a), so the father's rights to Article 345 The Civil Code was replaced with the provisions of Article 359 of the Civil Code, which states that the guardianship status of children under 18 years of age is determined by a judge.